RETRACTED: The approaches and methods of music psychology in the relationship between music emotion and cognition in music teaching activities - Jia, Nan; Yang, Chongze (Frontiers in Psychology, 2022)
In order to further improve the effect of music teaching, more music psychology should be applied in music teaching to assist teaching, and students should better understand the emotional elements reflected in music through music emotion and cognitive teaching. This essay starts from the relationship between music emotion and cognition, to deeply explore the application of music psychology in teaching activities, through the construction of music education psychological regulation function model to explore the effect of the application of psychology in music teaching. The results showed that the scores of positive emotions were significantly improved, while the scores of negative emotions were significantly decreased. The difference between the improvement and reduction of positive emotions was significant (P <0.01, P <0.01). The results show that psychology based on the relationship between emotions and people is helpful to improve the effectiveness of music teaching. And on this basis put forward the music teaching activity innovation path.